A Test of the Incremental Explanatory Power of Opinions Qualified for Consistency and Uncertainty - Hopwood, William; McKeown, James; Mutchler, Jane (The Accounting Review, 1989)
[The nature of auditors' qualified opinions gives rise to the belief that they can signal entity failure. This study examines the association between audit report qualifications and financial failure. Using the log-linear approach, the association between bankruptcy and audit qualifications is investigated for a univariate and two multivariate models. For the year immediately preceding bankruptcy, the univariate model tests indicate an association between consistency, going-concern, and other subject-to qualifications and bankruptcy. Tests of the multivariate models, which use audit report variables in conjuction with each other, indicate an association with bankruptcy for both the going-concern and other subject-to qualifications. When the audit report variables were tested jointly with a set of ratios comprising a bankruptcy-prediction model, the consistency and going-concern qualifications were still significantly associated with bankruptcy. The analysis also considered the predictive ability of the models while testing the sensitivity of the results to varying costs of Type I versus Type II errors. The results indicated that, in the majority of cases, the audit-opinion-only model is the least-cost alternative (ignoring analysis costs) in the last three years prior to bankruptcy. A naive strategy of predicting all companies as nonbankrupt performs as well as the statistical models in the fourth and fifth years prior to bankruptcy.]